2012
DOI: 10.1111/j.1365-2567.2012.03571.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced in vitro T‐cell responses induced by glutaraldehyde‐modified allergen extracts are caused mainly by retarded internalization of dendritic cells

Abstract: SummaryAlthough allergen-specific immunotherapy is a clinically effective therapy for IgE-mediated allergic diseases, the risk of IgE-mediated adverse effects still exists. For this reason, chemically modified allergoids have been introduced, which may destroy IgE-binding sites while T-cell activation should be retained. The aim of the study was to analyse the differences between intact allergens and differently modified/aggregated allergoids concerning their internalization as well as T-cell and basophil acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…Generally, the histamine and leukotriene release by basophils showed great donor variability. As expected from previous observations [22], mediator release was decreased strongly after stimulation with glutaraldehyde-modified allergoids compared to its native allergen extracts and formaldehyde-modified allergoids (Fig. 2).…”
Section: Decreased Histamine and Leukotriene Release By Basophils Aftsupporting
confidence: 90%
See 2 more Smart Citations
“…Generally, the histamine and leukotriene release by basophils showed great donor variability. As expected from previous observations [22], mediator release was decreased strongly after stimulation with glutaraldehyde-modified allergoids compared to its native allergen extracts and formaldehyde-modified allergoids (Fig. 2).…”
Section: Decreased Histamine and Leukotriene Release By Basophils Aftsupporting
confidence: 90%
“…Glutaraldehyde-modified alumadsorbed and unadsorbed allergoids led to a significantly decreased T cell proliferation and IL-2 production compared to the corresponding alum-adsorbed and unadsorbed native allergen extracts and formaldehyde-modified allergoids. This might be due to a more extensive aggregation and modification by glutaraldehyde treatment of our extracts, which was demonstrated previously by our group for unadsorbed allergens and allergoids [22]. In the study presented here, alum was not able to overcome the reduced T cell stimulatory capacity of glutaraldehyde-modified allergoids.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Some studies suggested that T cell responses are retained , whereas others showed that T cell responses can be reduced to a variable extent . GA treatment causes aggregation of proteins and may result in delayed uptake of the allergen by antigen‐presenting cells . In contrast to GA, unfolding of allergens from peanut (Ara h 2) and peach (Pru p 3) by RA treatment resulted in similar or slightly increased T cell proliferation , suggesting that unfolding may result in improved uptake, processing or presentation of the allergen.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]. Such drugs which lose their ability to interact with IgE antibodies are considerably safer and can be used at doses several times higher than doses of the standard allergen extracts.…”
Section: Introductionmentioning
confidence: 99%